Evaluation of Patient’s Satisfaction Level with the Provided Healthcare in Primary Healthcare Centers in Saudi Arabia - Puteh, Prof. Dr. Sharifa Ezat Wan; Aizuddin, Assoc. Prof. Dr. Azimatun Noor; Al Salem, Abdulaziz Abdullah (International Journal of Innovative Research in Medical Science, 2021)
The aim of this study was to evaluate patient’s satisfaction at primary health centers PHCCs in (Khobar, Jeddah, Riyadh, Jubail, Dhahran, Hail, Majmah, Abha, Baha, and Makkah) located in Saudi Arabia. The review finding shows that the highest overall satisfaction in Baha city (84.16%) followed by Majmah city with (81.7%), and the lowest overall satisfaction was the score (2.44) out of a maximum of 5 for Jubail city and Jeddah (2.45). Dhahran, Hail, Abha, Makkah, Riyadh, and Khobar were scored different scores; (3.66), (3.60), (57.7%), (70.1%), (64.2%) and (3.76). Nursing staff play a vital role in the satisfaction of patients in primary healthcare centers, including education, care and counselling, which is why all nursing staff should be skilled in clinical skills, level of education and interpersonal skills The highest domain of satisfaction was for nursing performance, and their treatment were found to be high (90.1%), but the lowest score was for the explanation of the medical conditions by the nurses, which could be due to language barrier. Medical care, laboratory services, and pharmacological services are other factors that may impact patient satisfaction with primary health centers. There are significant differences between Abha city (57.7%) and Baha city (84.16%) in south province in their overall satisfaction with Patient’s Satisfaction in primary healthcare centers PHCCs. And between Riyadh city (64.2%) and Majmah city (82.0%) in the middle province. In the eastern province, overall satisfaction for three cities Khobar city (3.76), Jubail city (2.44), and Dhahran city (3.66). The western province, overall satisfaction for two cities, Makkah city (70.1%), and Jeddah city (2.45). One city for north province Hail city (3.60). For comparison, the highest overall satisfaction in this study was Baha city (84.16%) located in south province, and the lowest one was Jubail city with score (2.44) out of 5.